Yam nematodes as production constraints in Ghana: a socio-economic perspective - Whedie, B.O.; Yami, G.M.; Nyaku, S.T.; Brentu, C.F.; Ankrah, D.; Dzidzienyo, D.; Bhattacharjee, R. (MDPI, 2025)
Yam (Dioscorea spp.) has been a prominent food and cash crop for most farmers in the yam production areas of Ghana, with the sales of yam in both domestic and international markets contributing significantly to the economy of the country. However, yam production by smallholder farmers is constrained by several challenges, including postharvest loss resulting from yam nematodes. This study conducted field surveys across seven districts across Ghana to collect data from randomly selected 150 yam farmers to investigate the status of nematode infestation, management practices and other socio-economic factors contributing to yam production in the country. The most common farm size for yam production from 2019 to 2022 was between 0.4 and 0.8 hectares. The majority of the farmers (56%) have been farming for over 15 years, with 6–10 years of experience in yam production, and preferred to use their own planting materials every year. Although most farmers (97.99%) experienced pests and diseases, most of them (77.33%) had no knowledge about nematode infestations in their farm causing damage to the tubers. Although yam farmers experienced yield losses, farmers were unable to manage nematode infestations in their farms. Twelve (12) genera of nematodes were identified in soils of yam rhizosphere across the seven districts. Tylenchus spp. (35.5%) and Scutellonema spp. (92.8%) were the most abundant nematode in soil samples and tuber peels, respectively while the second highest nematode in tuber peels was Meloidogyne spp. (4.0%). The presence of these parasitic nematodes in yam farms across Ghana suggests serious threats to the growth and yield of yams, although their presence is either not known or is usually neglected. Our result also confirmed the correlation between farmer storage practices and the management of nematodes, suggesting some storage practices such as barns may be effective in controlling nematodes. On the other hand, we find no association between pest occurrence in the field and nematode management. The lack of an association could be an indication that pest management in the field and nematode management in storage are separate activities and this underlines the importance of providing tailored postharvest training for smallholder farmers in effectively managing nematodes. It was therefore necessary to undertake this study and establish knowledge on the species as well as their prevalence in the farms across Ghana, contributing towards enhanced farmers’ understanding on nematode management and effective storage of yams to prevent losses caused by nematode infestation.